Neuropsychological Phenotype in Wolf-Hirschhorn Syndrome - Cossu, Maria Cristina; Albergo, Annalisa; Galluzzi, Claudia; Stefani, Cristiana; Antonucci, Gabriella (Journal of Intellectual Disability - Diagnosis and Treatment, 2014)
The Wolf-Hirschhorn syndrome (WHS) is a rare genetic disorder that causes a range of intellectual disability from mild to severe. In this study, we used standard tools to psychometrically characterize the specific neuropsychological phenotype of WHS. We studied 57 individuals with WHS, ranging in age from 2.6 to 28.6 years representing 70% of the certified Italian WHS population. Results obtained by administering Griffiths’ Mental Developmental Scales and the Vineland Adaptive Behavior Scale revealed a typical WHS neuropsychological phenotype characterized by specific strengths and weaknesses. Despite their severe cognitive impairment, in both scales, patients showed better communication and social interaction skills compared to visuo-motor abilities. Results of our study could bring to the development of new and more effective treatments for individuals affected by WHS: based on neuropsychological phenotype description, it should be possible to design specific rehabilitation programs. These programs would then be aimed at improving rehabilitation protocols to optimize the developmental potential and personal independence of individuals with WHS and thus to improve their quality of life.